THE UTILIZATION OF SHORT FILM MEDIA ENTITLED BERUBAH ON THE ABILITY TO WRITE SHORT STORY TEXT OF STUDENTS IN GRADE XI OTKP 1 SMK AS-SYAFI’IYAH JAKARTA ACADEMIC YEAR 2022/2023 - Irmandari, Ade (BAIK Publishers, 2025)
This study discusses the use of short film media entitled Berubah on the ability to write short story texts of class XI OTKP 1 students of SMK As-Syafi'iyah Jakarta. This study aims to (1) determine the writing skills of class XI OTKP 1 students of SMK As-Syafi'iyah Jakarta in writing short story texts (2) To determine that the short film media entitled Berubah is effective for learning to write short story texts of class XI OTKP 1 students of SMK As-Syafi'iyah Jakarta, and (3) To determine the results of the use of short film media entitled Berubah in learning to write short story texts of class XI OTKP 1 students of SMK As-Syafi'iyah Jakarta. The method used in this study is descriptive qualitative. The subjects of this study were 14 short stories created by class XI OTKP 1 students of SMK As-Syafi'iyah Jakarta in the 2022/2023 academic year. Data collection techniques in this study were observation, tests, interviews, and documentation. The assessment aspects in short story writing skills include the suitability of the story to the theme, the completeness of the elements/structure of the text, the accuracy of diction, and the accuracy of spelling and punctuation. The results of the study showed that the use of short film media in short story writing skills in students was declared successful with an average score of 80.35 and was included in the good category. The recapitulation results showed that 3 students with a percentage of 21% obtained a score with a very good predicate, 9 students with a percentage of 64% obtained a score with a good predicate, and 2 students with a percentage of 14% obtained a score with a sufficient predicate. Based on these data, it can be concluded that short film media is effective for use in learning short story writing skills.